ANALISIS KETERAMPILAN METAKOGNITIF SISWA DALAM MEMAHAMI PELAJARAN MATEMATIKA - Norli Trimawanti Purba; Nunik Ardiana; Sinar Depi Harahap (JURNAL MathEdu (Mathematic Education Journal), 2021)
The aim of the research is to analyze students’ metacognitive skill in understanding mathematics subject in SMP Negeri 3 Satu Atap Andam Dewi. The approach of the research is descriptive qualitative. Subject of the research consist of 6 students. Observation, test, and interview were used in collecting the data and triangulation technique was used in analysis technique. The research of the research shows the average of students’ metacognitive skill is 71.325 ( medium category). It means, students metacognitive in understanding mathematics subject include students have ability in conducting planning, monitoring in solving the problem, and giving the score by looking back.